DIC Score: Statistical Relationship with PT, APTT, and Simplified Scoring Systems with Combinations of PT and APTT. (5th March 2012) - Chandrashekar, Vani
Abstract : We looked into the statistical association of prothrombin time (PT) and activated partial thromboplastin time (APTT) with disseminated intravascular coagulation (DIC) score calculated using the International society for thrombosis and haemostasis (ISTH) scoring system. The PT, APTT, PT + APTT, and PT/APTT ratios were evaluated against the DIC score by linear regression analysis in fifty inpatients with suspected DIC. The PT, PT + APTT, and PT/APTT ratios were all found to be statistically significant in predicting DIC scores with P values of 0.02, 0.03, and 0.02, respectively. The APTT alone was not found to be statistically significant in predicting DIC score and had a P value of 0.09. This scoring system does not need d-dimer levels and the platelet count.